2020
DOI: 10.1071/an18737
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacillus subtilis PB6 enriched with choline to improve growth performance, immune status, histological parameters and intestinal microbiota of broiler chickens

Abstract: Context Probiotics used in poultry nutrition may promote the propagation of beneficial bacteria and limit the growth of pathogens, improving the body’s resistance to disease. Aims The aim of the study was to establish the dose and timing of administration of a probiotic preparation containing live cultures of Bacillus subtilis PB6 and choline that would have the most beneficial effect on histological parameters and microbiological status of the intestine, immune status, and growth performance of broiler chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…The histopathological photomicrographs revealed that supplementing broilers with 2.0 g/L B. subtilis probiotics could produce improved and near-normal histopathological pictures of livers and hearts with lymphoid hyperplasia in the bursas of Fabricius, thymuses, and spleens of broilers challenged with E. coli O157: H7 and S. Typhimurium. The current results were consistent with those reported by Abramowicz et al [73] and Adhikari et al [74], who revealed that B. subtilis supplementation in broiler chickens was able to enhance the histopathological structure of the intestine, improved intestinal microbiota actions, and enhanced its barriers to reduce the incidence of necrosis. Huang et al [75] also revealed that supplementing broiler chickens with C. butyricum probiotics improved the structure of the intestinal walls, reduced the incidence of necrotic enteritis, and enhanced the local immune response against pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 93%
“…The histopathological photomicrographs revealed that supplementing broilers with 2.0 g/L B. subtilis probiotics could produce improved and near-normal histopathological pictures of livers and hearts with lymphoid hyperplasia in the bursas of Fabricius, thymuses, and spleens of broilers challenged with E. coli O157: H7 and S. Typhimurium. The current results were consistent with those reported by Abramowicz et al [73] and Adhikari et al [74], who revealed that B. subtilis supplementation in broiler chickens was able to enhance the histopathological structure of the intestine, improved intestinal microbiota actions, and enhanced its barriers to reduce the incidence of necrosis. Huang et al [75] also revealed that supplementing broiler chickens with C. butyricum probiotics improved the structure of the intestinal walls, reduced the incidence of necrotic enteritis, and enhanced the local immune response against pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 93%
“…Bacillus subtilis (BS) is a commonly and widely used probiotic bacterium that can be incorporated in poultry diets for its beneficial advantages. A growing body of scientific studies reported that BS can improve the growth and laying performance (Neijat et al 2019;Abramowicz et al 2020;Hussein et al 2020). Additionally, a noteworthy improvement of the activities oxidative stress and immune response in chicken (Abramowicz et al 2019;Abudabos et al 2019;Park et al 2020), duck (Zhang et al 2016), and quail (Abdel-Moneim et al 2020) has been demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…There are reports indicating that some strains of probiotic bacteria also reduce inflammation of the intestinal mucosa by modulating the level of pro-inflammatory cytokines and other inflammatory mediators [57,58]. In studies by Krauze et al [14] and Abramowicz et al [19], the use of a probiotic containing Bacillus subtilis in the diet of chickens reduced the level of pro-inflammatory interleukin 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the birds' last day of life, elevated PC levels were not noted in either the small intestinal wall or the blood plasma of chickens receiving either the probiotic or the antibiotic. Literature data show that probiotics exhibit antioxidant activity [14,19,43]. Xue et al [43], in a study on laying hens receiving a probiotic containing B. subtilis strains, found that this supplement had no effect on the PC level in the muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation